Divine and Demonic Attributes in the Bhagavad Gita: Literal and Reflective Interpretation - Ghimire, Janardan (Interdisciplinary Research in Education, 2025)
The Bhagavad Gita, which is known as a core Vedic philosophical text, embraces different philosophical and practical aspect of human nature and teachings for the wellbeing of humankinds. Among varied contents, the divine and demonic attributes of human beings appear in the sixteen chapter. This article aims to interpret the divine and demonic attributes from literal and reflective interpretation adopting the ‘nine steps rendition’ and hermeneutic methods of text interpretation. In a literal sense, fearlessness, peace, purity, spirituality, charity, self-control, non-violence, truthfulness, kindness, love, empathy, etc. are divine qualities which make an individual divine. On the contrary, ego, pride, anger, fear, greed, attachment, ignorance, atheism, wrong actions, terror, impurity, wrong thoughts, apathy, cruelty, truth, etc. are demonic qualities that make a person sinful or evil. These two attributes explained by the Bhagavad Gita can be seen in every individual in the world and can also be reflected in oneself. While there is a lack of divine qualities in the world but demonic quality is proliferating throughout the world as a great empire. Due to the demonic attributes, the world community has to deal with terrible social problems. These attributes are initially psychological as well as social. The most effective medicine for the demonic diseases of the individual's mind and society is education. Education transforms individuals and societies with the demonic into the divine attribute, so it has educational significance, too. Although there is a lot of practical knowledge in the Vedic and indigenous scriptures, the knowledge has not been explored and reinterpreted. It seems that scholars and academic institutions should pay due attention to this issue.